A methods engineering study on Lapid Foods - David, Abigail Louise; Kempis, Seigfriend; Villasanta, Rosarie Raysalyn (Diliman, Quezon City College of Engineering, 2004)
There were three main areas of problems identified-plant layout and location, equipment design, and working conditions. The layout of the plant as a whole was contributing much to the inefficiency of the plant, mainly because the different areas within the plant were too far apart. Thus, much time is wasted in transporting raw, intermediate and finished goods to and from each area. There were no promising immediate solutions to the problems regarding the plant layout and location, basically because there is very little area for expansion in the vicinity. It is not possible to bring the different areas closer in the existing setting. However, rearranging the different workstations within the chopping area, the time and distance traveled by the materials may be reduced. For the grinding area, the removal of the vinegar packing station from the area will widen the area for the crushing and grinding operations, and will thus ease the movement of workers and materials within the area. Implementation of these suggestions may be conducted without any additional cost, but may need an adjustment period for the workers. In addition, it is also possible to ease the problem regarding transportation by improving on the existing conditions of the ramp. The replacement of the ramp flooring with appropriate non-skid tiles will shorten the time needed to transport materials to and from the second and third floor. This, along with the installation of railings, will also provide improved safety and reduced fatigue for the workers. These suggestions will entail costs, both due to the construction costs and the production loss during the construction, but may prove crucial to the aim of increasing productivity. However, the construction should be strategically scheduled to reduce the impact on production. Regarding working conditions, it is imperative to improve the existing conditions within the cooking area. At present, the cooking area's temperature is far above the normal working temperature and is causing much fatigue to workers. It is very important to improve the ventilation within the area. To do this, it would be helpful to install additional industrial ventilator fans to serve as exhaust for the hot air. In turn, it should be complemented by expanding existing windows, to serve as a source of fresh air for the area. There would be equipment and construction costs upon the implementation of these proposals, but hopefully minimal effect on the production and future operating expenses. The improvement in the temperature within the area should significantly improve the conditions of the workers assigned within the area, reducing worker fatigue and accordingly reducing the need for more workers manning the area. Several equipment designs also appeared to be contributing to the fatigue experienced by the workers. One of these is the chopping board, which is too high for the worker of average height. It should be designed such that shorter workers may be able to comfortably use it, at elbow height. Thus, the height of the chopping board should be reduced, possibly by buying or making new ones. The grinder is also at an awkward height for the worker. To aid this, a simple step stool of appropriate height should be provided for the worker. The step stool may be bought or just fabricated by the maintenance staff. In addition, the equipment used to sift the crushed chicharon is very heavy and causes strain on the arms of the worker. The problem may simply be solved by creating a frame that will support the weight of the sifter, similar to those used in construction sites. Another solution that may be done in conjunction to or alternate to the one previously mentioned is by designing and fabricating a new sifter made of a lighter material. All these equipment improvements and replacements would entail minimal cost. Among the other problems is concerned with the work assignment. There was a bottleneck identified after the de-fatting procedure for the production of chicharon balat. This was mainly because there was only one worker assigned to collect and chop all the pork skin after de-fatting while there were seven workers de-fatting the pork skin. Solution to this would simply be reassignment of the workers, either by assigning an additional chopper or assigning a collector to assist the chopper. The abovementioned proposals generally intend to reduce worker fatigue, minimize travel time of materials, and eliminate bottleneck operations. These should primarily improve the operations of the company to allow further expansion by maximizing time utilization and worker productivity.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Food industry and trade; Systems analysis